Die Kontinuität im kanonischen Recht - May, Georg 1926- (2003)
Erstveröffentlichung in: AKathKR 135 (1966), 52-92
Keywords: Kanonisches Recht; Kirchenrecht; Rechtstheologie; Ius divinum; Kirchengeschichte; Recht; Geschichte